Microstructural Changes of Bone after Soft Tissue Removal: ATR-FTIR and XRD Spectroscopies - Alebrahim, Mohammad A.; Al-Akhras, M-Ali H.; Al-Hiyasat, Ahmad S.; Ba Rajjash, Ali S.; Mousa, M. S.; Al Darayseh, Abdulla (Journal of Spectroscopy, 2023)
The structural alterations that may arise in boiled and nonboiled bones are often overlooked despite their critical importance in the development of defleshing techniques across various scientific disciplines. To elucidate the microstructural characteristics of bones following the removal of soft tissue through conventional methods, attenuated total reflectance Fourier-transform infrared (ATR-FTIR) and X-ray diffraction (XRD) spectroscopies were employed. Our findings indicate that the boiled water method resulted in higher crystallinity, as evidenced by the FTIR data, whereas the XRD data revealed the opposite. This underscores the notion that a direct comparison between these two techniques is unfeasible as they measure distinct crystallinity parameters. In addition, the cold water maceration method caused a significant reduction in collagen crosslinking, as evidenced by the lower index observed.